Service Export Sophistication and Europe’s New Growth Model - Gable, Susanna Lundstrom; Mishra, Saurabh (2012)
Technology has changed the nature of service activities and made them more productive, tradable and fragmented in the global supply chain. Has Europe's growth been benefiting from the ongoing globalization of services? Services dominate growth in EU-15 countries and, to a lesser extent, in New Member States (NMS) and Accession (ACC) countries. Except in the ACC region, Europe has maintained specialization in service exports. Service productivity, tradability, and exports of modern services are high in EU-15, growing fast in NMS while at a lower pace in ACC. Service export sophistication is important for growth across the region, but especially in NMS.